Mechanical, thermal and acoustical characteristics of composite board kneaded by leather fiber and semi-liquefied bamboo. (18th July 2022) - Pu, Hongxia; Shu, Caihong; Dai, Rui; Chen, Hui; Shan, Zhihua
Graphical abstract: Highlights: The addition of SLB improves the mechanochemical interaction between leather fiber and bamboo fiber, which provides reliability for kneading and manufacturing of composites. The composite board made from the two wastes have good heat insulation and sound insulation function and have potential engineering application value. The prepared plastic board has good mechanical properties. The smashing realizes the homogenization of bamboo and leather, overcomes the defects of the two types of wastes, and makes the wastes obtain value-added utilization. Abstract: Collecting waste and using it to prepare value-added products with better performance is the need of the times. Considering this goal, the experiment has completed the work of preparing value-added boards using leather fiber (LF) and semi-liquefied bamboo fiber (SLB). First, the feasibility of mechano-chemical action is determined by kneading two fibers, and then, the composited board was prepared by the response surface method, in which the thermoplastic polyurethane elastomer (TPU) and silane coupling agent (KH550) were used to improve the hydrophobicity and physicomechanical properties in this experiment. When the composition (by weight) of composited board (LBTK board) is 160 % LF, 100% SLB, 40% TPU (based on LF), 20% KH550 (based on TPU) and the kneading time is 23 min at 78 ℃, the integrated performance of the LBTK board meets the main index of the physicomechanical properties of the LBTK board in the national standard GB/T 24137–2009 "Wood Plastic Decorative Board". The thermal insulation and sound absorption properties of the LBTK board were also evaluated, including the thermal conductivity (0.0502 W/m·K) and the sound transmission loss (25 ∼ 45 dB) in the range of 500 ∼ 14000 Hz. Finally, using a scanning electron microscope (SEM), thermogravimetric analysis (TG), differential scanning calorimeter (DSC), the surface morphology, hydrophobicity, and thermal stability of the LBTK board were measured. The results show that the LBTK board has the potential application value and the experiment also provides a way to recycle the two kinds of waste.